Impulsivity and self-harm in adolescence - Lockwood, Joanna (2019)
This thesis explores the relationship between dimensions of trait impulsivity and self-harm outcomes in school and college-based young people, drawing on a multi-method approach. Adolescence, and in particular early to mid-adolescence, is a vulnerable time for developing self-harm and this vulnerability may be amplified by levels of impulsivity and emotional reactivity which are also elevated during this period. Impulsivity is a broad, multi-faceted construct, the various dimensions of which have historically included the failure to analyse and reflect before engaging in behaviour, or to adequately think through the consequences of action. Recently, emotion-based dispositions towards rash action (Negative and Positive Urgency) have been differentiated from other non-emotion-based forms of impulsivity. Considerable empirical and theoretical work has implicated impulsivity across a range of problem behaviours in youth, yet the relevance of the construct in understanding and identifying behaviour engagement has been hampered by a failure to adequately specify which dimension of impulsivity is associated with the outcome of interest. Research is starting to specify with greater precision how impulsivity relates to self-harm behaviour in youth. This work is facilitated in large part by the delineation of unidimensional impulsivity traits within the UPPS-P (Urgency-Premeditation-Perseverance-Sensation-Seeking) Impulsivity model (Lynam, Whiteside, Smith, & Cyders, 2006; Whiteside & Lynam, 2001). The present thesis aims to contribute to this emerging body of work by empirically examining how unidimensional impulsivity traits are implicated in adolescent self-harm across different developmental stages and within cross-sectional, prospective and qualitative designs. As such, the work aims to deliver a body of evidence to guide future intervention and prevention work in this field. Ethical reflexivity should be central to any research endeavour and is particularly pertinent within the field of mental health. Additionally therefore, the thesis has engaged with the ethical impact of this body of work on the young people involved.